Decreased activities of daily living at discharge predict mortality and readmission in elderly patients after cardiac and aortic surgery: A retrospective cohort study. Issue 31 (6th August 2021) - Sato, Masaaki; Mutai, Hitoshi; Yamamoto, Shuhei; Tsukakoshi, Daichi; Takeda, Shuhei; Oguchi, Natsuko; Ichimura, Hajime; Ikegami, Shota; Wada, Yuko; Seto, Tatsuichiro; Horiuchi, Hiroshi
Abstract : Abstract: Recently, activities of daily living (ADL) were identified as a prognostic factor among elderly patients with heart disease; however, a specific association between ADL and prognosis after cardiac and aortic surgery is not well established. We aimed to clarify the impact of ADL capacity at discharge on prognosis in elderly patients after cardiac and aortic surgery. This retrospective cohort study included 171 elderly patients who underwent open operation for cardiovascular disease in a single center (median age: 74 years; men: 70%). We used the Barthel Index (BI) as an indicator for ADL. Patients were classified into 2 groups according to the BI at discharge, indicating a high (BI ≥ 85) or low (BI < 85) ADL status. All-cause mortality and unplanned readmission events were observed after discharge. Thirteen all-cause mortality and 44 all-cause unplanned readmission events occurred during the median follow-up of 365 days. Using Kaplan–Meier analysis, a low ADL status was determined to be significantly associated with all-cause mortality and unplanned readmission. In the multivariable Cox proportional hazard models, a low ADL status was an independent predictor of all-cause mortality and unplanned readmission after adjusting for age, sex, length of hospital stay, and other variables (including preoperative status, surgical parameter, and postoperative course). A low ADL status at discharge predicted all-cause mortality and unplanned readmission in elderly patients after cardiac and aortic surgery. A comprehensive approach from the time of admission to postdischarge to improve ADL capacity in elderly patients undergoing cardiac and aortic surgery may improve patient outcomes.